2009
DOI: 10.1016/j.biortech.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the acidity of rapeseed oil on its transesterification

Abstract: SummaryThe aim of this work is to study the transesterification of vegetable oils with a high acid number. Rapeseed oil was used as the raw material and its acid number was changed by the adding of oleic acid (from 0.89 to 12.25 mg KOH/g). Methanol was used for transesterification (molar ratio of oil to methanol 1:6) and potassium hydroxide was used as a catalyst. After the reaction time, the residue of catalyst was neutralized by gaseous carbon dioxide and methanol excess was removed. After the separation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 15 publications
(11 reference statements)
1
23
0
2
Order By: Relevance
“…Therefore, no kinetic models, equilibrium constants and concentrations of intermediates were needed. This work extends our previous work (Kwiecien et al, 2009) dealing with the effect of the oleic acid (formed neutralisation water respectively) artificially added into the oil by a statistical enumeration of water effect and also it is extended by the effect of the catalyst amount.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…Therefore, no kinetic models, equilibrium constants and concentrations of intermediates were needed. This work extends our previous work (Kwiecien et al, 2009) dealing with the effect of the oleic acid (formed neutralisation water respectively) artificially added into the oil by a statistical enumeration of water effect and also it is extended by the effect of the catalyst amount.…”
Section: Introductionsupporting
confidence: 60%
“…According to our previous work (Kwiecien et al, 2009), no conversion decrease was observed, whereas these two models for the conversion express the opposite. That could mean that the simulation of higher acidity (i.e.…”
Section: Model Of Oil Conversion To the Mementioning
confidence: 93%
See 2 more Smart Citations
“…Although there are no official regulations for properties of oils used as raw material for biodiesel production, the acidity level is expected to be below 2 mg KOH·g -1 (Kwiecien et al, 2009). The moisture content found in M. Pubescens oil is 0.88%.…”
Section: Acidity Level Peroxide Value and Moisture Contentmentioning
confidence: 99%